Sustainable tourism investment as a modern approach to protecting tourist areas and achieving sustainable development. - slimani, malika (Journal of Research in Finance and Accounting, 2025)
This study aims to identify the dimensions of sustainable tourism, And the local and international orientation through studying their orientations towards sustainable tourism investment. The study followed the descriptive approach by studying and presenting successful international experiences in the field of sustainable tourism With a set of stats analysis. Results: There is a difference in global trends towards sustainable tourism, and this is due to the culture of society and the legal systems of each country, The Costa Rica experience is a vivid example of sustainable tourism, as it achieves both its financial and environmental goals, as it ranks first in the world in sustainable tourism, It is currently working on achieving 100% sustainable tourism by 2025. Through this study, we concluded the necessity of imposing international and local laws to achieve sustainable tourism is one of the most important factors affecting changing the behavior of tourists and tourism institutionsTop of Form Bottom of Form